An examination of base erosion and profit shifting exposure for South Africa - Bob, Vanessa (My University, 2016)
Base erosion and profit shifting (BEPS) is a key concern in international tax. In 2010 the Organization for Economic Co-operation and Development (OECD) was tasked with the study of BEPS. In 2013 the OECD released the study report “Addressing base erosion and profit shifting” emphasising BEPS and the risk for the world’s economies and tax bases. The OECD has been focused on BEPS due to several reasons, namely; increase in globalisation, an ever-changing digital economic environment, mismatches of different countries’ tax legislation and the ease with which intellectual property can be transferred. They has released several documents detailing the risk of BEPS as well as an action plan outlining their aim for the transformation of local and international tax. According to the OECD corporate income taxes, as a percentage of gross domestic product (GDP) is a possible indication of base erosion. In South Africa, the corporate income tax rate as a percentage of GDP has decreased from 7.2 % in 20081 to 5% in 20132. Is this a possible indication of base erosion or profit shifting taking place? Protecting South Africa’s tax base is paramount for future growth of the country and the economy. It is therefore important to identify whether BEPS is a real risk and to determine whether South Africa has adequate legislation in place to protect its tax base. Keywords: Base erosion and profit shifting, BEPS, Organisation for Economic Co-operation and Development, OECD, international tax, transfer pricing, thin capitalisation, treaty abuse, treaty shopping
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation) Johannesburg, 2014
Keywords: Base erosion and profit shifting; BEPS; Organisation for Economic Cooperation and Development; OECD; International tax; Transfer pricing; Thin capitalisation; Treaty abuse